Pedagogical tourism in national parks: relations between Brazil and Portugal - Fonsêca, Flaviano Oliveira (2020)
Tourism has established itself as an important economic and social activity in almost all world scenarios, with emphasis on the segments related to nature. With this, the Conservation Units have significantly corroborated the quality of the offer of spaces where it is possible to practice this type of tourism. In this work, we will highlight the potentialities and possibilities of the practice of Pedagogical Tourism in the national parks of Serra de Itabaiana, in Brazil and Peneda-Gerês, in Portugal. To achieve the objective, this research requested documentary and bibliographic analysis from the public data platforms of the countries in question and proceeded to the consultation of documents provided by the Institute of Nature Conservation and Forests, Portugal. Interviews were conducted with the most important managers of both Conservation Units. It was concluded that the parks under study already perform the function of living laboratory for the practice of pedagogical tourism and, therefore, are potentially expressive and recognized by research institutions of both countries. However, it should be noted that economic sustainability has proved problematic for the analyzed realities and requires public and private interventions in order to make them more effective and sustainable for the improvement of man and nature relations.